Advancing traceability using DNA sequence on seafood product: fraudulence in shrimp crackers (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nurilmala M, Atjitama Y, Jacob AM, Indarwati AR, Nugraha R. 2020. Advancing traceability using DNA sequence on seafood product: fraudulence in shrimp crackers. Biodiversitas 21: 5650-5656. Shrimp crackers are snacks made from starch with the addition of shrimp and other ingredients. Authentication of shrimp crackers becomes a quality control method in line with its traceability since the morphological characters are not recognized in those products. The failure of the authentication will lead to adulteration of shrimp products. The study aimed to design shrimp-specific polymerase chain reaction (PCR) primers by and used them to authenticate shrimp cracker products to assure their traceability. The primers were designed from cytochrome oxidase subunit I (COI) gene with a GC content of 50% and a melting temperature of 57 °C. The amplicon had a length of 613 bp. Fourteen shrimp crackers having DNA concentrations 0.3 to 8.1 ng/µL were evaluated. Eight out of fourteen DNA samples were successfully amplified using the specific primer and could be visualized on the agarose gel at 500-750 bp. Those DNA samples were identified belonging to shrimp species, namely Litopenaeus vannamei, Metapenaeus ensis, and Fenneropenaeus merguiensis with 95% to 100% identity. Meanwhile, the other six DNA samples underwent PCR using universal primers. One sample was amplified and identified as fish (Sphyraena flavicauda). These results indicate illegal substitution of shrimp using unidentified species occurred in shrimp crackers.
Keywords: Adulteration, cytochrome oxidase subunit I, PCR, shrimp, specific primer